O processo de profissionalização de uma ocupação feminina: a fonoaudiologia em São Paulo - Kernbichler, Maria Alice Borin Sanchez (2005)
This work has for objective analyze the speech therapy under the approach of the Sociology of the Professions, private field of the Sociology of the Knowledge. The choice relapsed about that profession that is going to accompany the specificity of the journey of a female occupation, to the long one of the time. That is going to articulate questions concerning the world of the work in his field named profession, with the dimension of kind, for understand as those two aspects marks do of the speech therapy. In that analysis, we flow as are prosecuted the relations between the professionals besides the power that some professions exercise about other and the impact of the composition of kind about those characteristics, since the profession is constituted in its big majority by women. To research prioritizes the oral history and based itself mainly in 18 interviews with statements of speech therapists that his professional paths related us providing us the analysis of as the trial of professionalization of the speech therapy is marked by the articulation between kind and profession.